PERANAN PERENCANAAN SISTEM INFORMASI TERHADAP KUALITAS SISTEM - DEVI, CHENLIA (Berkala Ilmiah Mahasiswa Akuntansi)
Increasing competition that exists in the business world, making company faces the challenge of how to keep abreast developments information systems that aim to facilitate company in operation or performance. Enterprise planning system quality of existing systems will be able support a firm's performance.Planning system is a stage that used to create system in addressing problems facing company. By doing the planning system will certainly result in a new system which will be developed. In conducting a planning system there are several processes that must be done to produce new system. System planning process consists of: planning system projects, prepare projects and the system defines the projects developed. Planning system will affect the quality of the resulting system. The quality system can be seen from: ease of use,access, speed access and security systems. The quality system can be from the costs and benefits doing a plan. Benefits can be seen from the accuracy, timely, access, flexibility and efficiency of the resulting system. Given the costs and benefits in planning system then can used to measure system's success and quality of the resulting system of planning system. So that planning system can influence the quality resulting system of company.